The new functional accuracies for Maxell and Kelvin–Fought linear rheological models - E. M. Kartashov (Тонкие химические технологии)
The new functional accuracies for the description of mechanical models of polymer solids are proposed. The examples of rheological Maxwell model and Kelvin– Fought model are considered.